BASIC DIRECTIONS OF MODERN PHYSICS AND ASTRONOMY AND THEIR ROLE IN THE DEVELOPMENT OF INNOVATIVE DEVELOPMENT - Saydayev, Obid (Физико-технологического образование, 2023)
In this article bases of formation of the purposes of modern physics are discussed. Literally translated from Greek, the word "physics" means "nature", therefore, physics is the science of nature, studying the simplest and at the same time the most general properties of the material world. Physics is the main of the natural sciences, since it reveals truths that are valid for the entire universe. The laws of physics are the basis of knowledge about the structure and functioning of the Universe, they underlie the scientific comprehension of reality. Two circumstances make it difficult to understand modern physics: the use of the most complex mathematical apparatus and the inability to create a visual model of modern physical concepts are associated with the gradual rejection of direct visibility. This is due to the fact that some aspects of reality are invisible to superficial observation and visibility can be misleading. It turned out to correspond to reality simply because it was not noticed that the reason for the body to stop is friction. In order to draw a correct conclusion, an experiment was required, which was not a real experiment, impossible in this case, but an ideal experiment